Relationship of Lifestyle with the Event of Hypertension in Young Adults in Community - Aesthetica Islamy; Yitno Yitno (CV. Global Health Science Group, 2020)
Hypertension is a disease whose cases can increase in both urban and rural communities. The occurrence of hypertension in young adults is influenced by lifestyle, such as lack of exercise or physical activity, smoking, stress, and alcohol consumption. The habits of the tile industry workers in Notorejo Village every time they consume cigarettes and coffee, even when working there are also those who consume cigarettes. The purpose of this study was to determine the relationship of lifestyle with the incidence of hypertension in young adults in Sumber RT 03 RW 05 Notorejo Village, Gondang District, Tulungagung. The type of study is association analytic with cross sectional technique.This study uses a correlation method using a cross sectional approach. The population is all young adult communities in Sumber RT 03 RW 05 Notorejo Village Gondang District Tulungagung regency as many as 250 people using a quota sampling technique obtained as many as 30 respondents. Data collected by observing distributing questionnaires then processed by editing, coding, scoring, tabulating and tested using the Spearman-rho Test. The results showed who have a good lifestyle as many as 19 respondents (63.3%) while respondents who have a bad lifestyle obtained 11 respondents (36.7%). In the event of hypertension, respondents who had optimal blood pressure obtained 6 respondents (20%), normal obtained 11 respondents (36.7), stage 1 hypertension obtained 3 respondents (10%, stage 2 hypertension obtained 5 respondents (16.7%) , stage 3 hypertension obtained 3 respondents (10%) and stage 4 hypertension obtained 2 respondents (6.6%). Data analyzed with Spearman-Rho Test and obtained Pvalue of 0.021, because Pvalue <α (α = 0.05) then H1 was accepted and H0 was rejected, which means there is a lifestyle relationship with the incidence of hypertension in young adults in Sumber Hamlet community RT 03 RW 05 Notorejo Village Gondang District Tulungagung Regency. From the results of these studies it is concluded that the better the people's lifestyle, the lower the incidence of hypertension, conversely, the worse the people's lifestyle, the higher the incidence of hypertension. Lifestyle is very important and a major factor in the incidence of hypertension. By improving lifestyle, it will significantly reduce the incidence of hypertension. The impact of a worsening lifestyle is to increase the incidence of hypertension so that the best solution in the results of this study is that researchers hope people suffering from hypertension to improve their lifestyle such as eating low salt, not smoking, not stressing and getting enough sleep.